Influence of Satlogi Santri Values on Sufistic Leadership: Enhancing Service Quality and Productivity in Pesantren - Fauzi, Ahmad; Dakir, Dakir; Qodir, Abdul; Fatchurahman, M; Minarti, Sri (Prodi Manajemen Pendidikan Islam Pascasarjana Institut Pesantren KH. Abdul Chalim Mojokerto, 2025)
This study examines the influence of satlogi santri values on the development of Sufistic leadership at Pesantren Zainul Hasan Genggong Probolinggo, with a particular focus on their impact on service quality and individual productivity. Adopting a qualitative design, data were gathered through interviews, observations, and documentation. The findings indicate that the habitualization process occurs in three stages: externalization, in which values are articulated and transmitted by pesantren leaders; objectivation, in which these values are institutionalized through daily practices and rituals; and internalization, in which values such as humility, sincerity, and integrity become embedded in leaders’ behaviors. This process fosters a leadership style that emphasizes ethical conduct, exemplarity, and accountability. As a result, Sufistic leadership improves communication, strengthens trust, enhances service quality, and promotes a productive work culture. The study concludes that Sufistic leadership provides not only a solution to the ethical leadership crisis in educational institutions but also a practical framework for pesantren and other Islamic educational settings to cultivate sustainable organizational culture and improve overall institutional effectiveness.